Analisis Faktor yang Memengaruhi Penggunaan Shopee sebagai Aplikasi E-Commerce pada Mahasiswa - Kinanty Ajeng Sulistiawati; Osly Usman; Ayatulloh Michael Musyaffi (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The development of digital economic technology has triggered a shift from conventional to electronic-based transaction patterns in Indonesia, with Shopee dominating as the most popular e-commerce platform among students. This study aims to analyze the influence of Technology Acceptance Model (TAM) factors on the sustained actual usage of the Shopee application among active students in the Greater Jakarta (Jabodetabek) area. A quantitative causal approach with a survey method was employed, using an online questionnaire based on a 1–6 Likert scale distributed to 200 active student respondents from five State Universities (PTN) in Jabodetabek through purposive sampling. The primary data were analyzed using Structural Equation Modeling (SEM) operated through Confirmatory Factor Analysis (CFA), along with mediation testing using the Sobel test. The empirical results reveal that all twelve proposed hypotheses were accepted, showing positive and significant effects. Perceived ease of use proved to be the key driver in enhancing perceived usefulness, attitude toward use, and behavioral intention among students. Furthermore, attitude and behavioral intention were found to serve as effective mediating variables, transforming psychological motivation into actual, routine use of the Shopee application in daily activities. These findings are expected to contribute theoretically to the TAM model and offer practical recommendations for marketing strategies in the digital retail industry.